ANALYSIS DIRECTIVE UTTERANCES IN THE VENOM MOVIE MANUSCRIPT - Agus syahid; Ida Bagus Tri Istyadi (LPPM Universitas Bumigora Mataram, 2018)
This research describes about directive utterances in the Venom movie manuscript. The aim of this research is to identify form of directives and classify the function of directives utterances. To identify and classify directive utterances, researcher uses specch act theory (locutionary, illocutionary, and perlocutionary act). The data source of directive utterances is in the movie The Venom manuscript. The researcher uses observation and documentation methods in gathering data. This research uses descriptive qualitative method. The result of this study shows that the most of directive utterances in the movie The Venom manuscript is imperative sentences (13 data or 60%), declarative sentences (6 data or 30%), and introgative sentences (1 data or 10%). The function of directive is commanding, suggesting, requesting, and prohibiting.